Validation of the name Paraphlomis hispida C.Y. Wu (Lamiaceae) - Chunlei, Xiang; Hua, Peng (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. Keywords: Paraphlomis hispida; Lamiaceae; Nomenclature; Validation; China DOI: 10.3329/bjpt.v15i1.930 Bangladesh J. Plant Taxon. 15(1): 73-74, 2008 (June)